Design and development of the PLC based sensor and instrumentation system for self-propelled pruning residue mulcher prototype - Unal, Ilker; Canakci, Murad; Topakci, Mehmet; Karayel, Davut; Cakir, Mehmet (ELSEVIER SCI LTD, 2021)
The main idea of this paper is to present a programmable logic controller (PLC) based data acquisition, telemetry, and control system for self-propelled pruning residue mulcher prototype. The main power source of the mulcher prototype is the diesel engine. Hydraulic systems were used to transmit the motion received from the motor to the wheels, pick up and mulching unit, and steering systems. The operation and control of all systems were carried out using a PLC-based electromechanical system. The objective of this paper is to develop a PLC-based measuring and controlling system in order to control, collect, and monitor the sensor-based data such as: number of cycles of the fingers in the pick-up unit, the speed of the mulcher blades, machine forward speed, fuel consumption, and pump pressures. In the system, an embedded industrial computer and differential global positioning system (DGPS) were used to assist in real-time measuring, recording, controlling, and displaying all the sensor data during the field operation. The control of the machine is built using industry-standard off-theshelf PLCs. The data acquisition software was written using VB.NET programming language. The PLC-based sensor and instrumentation system was tested and validated on different orchards. Test results show that the developed control and data acquisition system is well qualified with high control precision and high reaction speed. The developed machine is the first self-propelled agricultural mulcher machine developed in Turkey. And there is no other example in the world in terms of using PLC-based control and data acquisition system in selfpropelled pruning residue mulchers.
Keywords: Self-propelled pruning residue mulcher; PLC-based control; Sensor and instrumentation system; Data acquisition system; CHOPPER; Agriculture; Computer Science